FELLAHEEN SMUGGLING FROM THE MOUNT LEBANON - Günaydın, Meryem (My University, 2021)
Fellaheen from Mount Lebanon joined the large scale immigration flow that started in America inthe 19th century, too. The flight of fellaheen fromthe people of Mount Lebanon to America was theresult of an organized smuggling from land toport and port to ferry. The increasing fellahmigration has become the focus ofcorrespondence between Istanbul and Beirut. Anumber of new procedures and measures havebeen brought to the agenda and implemented tocombat fellah trafficking.In the migration flows from Mount Lebanon toAmerica or other foreign countries, theimmigration of the rural cultivators, namely thefellaheen, has a special importance. In order tounderstand the course of this migration, it isaimed to examine the subject, and the story offellah smuggling will be explained through themeasures taken and its effects in this study.
Keywords: Tarih